Implementation Of Neural Network With Perceptron Method For Letters Or Text Recognition - Ekatri Ayuningsih; Eko Afrianto (INFOKUM, 2021)
Modeling with neural networks is the learning and adjustment of an object. The perceptron method is a learning method with supervision in a neural network system. In designing a neural network that needs to be considered is the number of specifications that will be identified. A neural network consists of a number of neurons and a number of inputs. In identifying some letters, it takes several neurons to distinguish them. These neurons will generate a combination value that is used to identify the letters.so that the resulting network must have parameters that can be set by changing through the rules of learning with supervision. In this case, the identification of letters and numbers will be discussed. Visual basic 6.0 is used to simulate the learning process using the perceptron method